Understanding determinants of preferences for autonomous vehicles in the global south: Private, shared, or pooled rides in Bangkok, Thailand - Phathinan Thaithatkul; Saksith Chalermpong; Lisa Kenney; Apiwat Ratanawaraha (Transportation Research Interdisciplinary Perspectives, 2024)
The effects of AVs on cities remain uncertain but will ultimately be shaped by the predominant service model—either private ownership or shared usage. People’s decisions about which one to use are based in part on individual perceptions and preferences. To date, there have been only a handful of studies on AV preferences from the Global South, yet these countries may benefit greatly from AVs, but they also present a unique set of challenges for implementation. This study therefore fills some important research gaps about understanding preferences across different AV service models (i.e., privately owned AVs vs. shared AVs) and ride types (i.e., solo vs. pooled rides). From our stated preference research in Bangkok, Thailand our respondents show somewhat low interest in AVs overall, but we also found that men, people with higher incomes, and those who currently travel by private vehicles and those who use public transport all show more interest in privately-owned AVs over shared AVs (SAVs). However, being a public transport user increases interest in pooled SAVs, and income was not a significant effect on interest in SAVs. Our study revealed that people interested in SAVs would also be interested in pooled ride SAVs, and vice versa. These results can help inform policy and regulatory areas that need to be addressed for sustainable, accessible and inclusive AV implementation in Thailand. We also discuss the broader implications for future research about AV preferences in the Global South.